PENGARUH PELAYANAN, KUALITAS PRODUK DAN HARGA TERHADAP KEPUASAN PELANGGAN PADA WARUNG BAKSO BANDUNG DI TENGGARONG - Saldon Silitubun; Silvana Wijayanti; Farida Aryani (I-Con Media, 2024)
Warung Bakso Bandung as one of the sales businesses, one of the things that need to be considered is the level of customer satisfaction, this concerns service to customers who come to make purchases and prices that can influence consumers to make purchases. The purpose of this study is to determine the effect of service variables, product quality, and price on customer satisfaction at Warung Bakso Bandung in Tenggarong. To determine the effect of partial and significant service variables on customer satisfaction at Warung Bakso Bandung in Tenggarong. To determine the effect of product quality has a partial and significant effect on customer satisfaction at Warung Bakso Bandung in Tenggarong. To determine the effect of price variables partially affecting customer satisfaction at Warung Bakso Bandung in Tenggarong. The results of the research obtained are the results of the calculation of test F (simultaneous correlation / together), it can be said that the variables of service (X1), product quality (X2) and price (X3) together (simultaneously) are able to show their influence on customer satisfaction. Service variables have a positive influence on customer satisfaction. Product quality variables have a positive influence on customer satisfaction. Price variables have a positive influence on customer satisfaction.